Implementasi Model Pembelajaran REACT untuk Meningkatkan Hasil Belajar Siswa Kelas IV Pada Pelajaran Matematika - Handayani, Ucik; Cica Oktiani (Kilau Publishing, 2024)
The mathematics learning process at SDN 40 Seluma is dominated by students working on problems in books, so that mathematics learning outcomes are less than optimal. One of the efforts that can be made is by applying the REACT learning model (Relating, Experiencing, Applying, Cooperating, and Transferring). The purpose of this study was to improve the learning outcomes of fourth grade mathematics students at SDN 40 Seluma by applying the REACT learning model. The research subjects were 15 students. This research is a type of classroom action research by implementing learning improvements as many as 2 cycles including several stages namely planning, implementation, observation and reflection. The results showed that the application of the REACT learning model can improve mathematics learning outcomes in grade IV students of SDN 40 Seluma. This is shown from the classical completeness of student learning outcomes, namely pre-cycle only 46.7% increased in cycle I to 73.3% and in cycle II to 86.7%. Based on the results of this study can be used as material in the next learning process so that student learning outcomes can improve. This research is limited to grade IV mathematics subjects, it is highly recommended to apply the REACT learning model at other grade levels and subjects in order to expand knowledge and develop the results of this research.